EVALUASI KEBIJAKAN PENDIRIAN PASAR IKAN HIGIENIS MINA REJOMULYO KOTA SEMARANG - Bayu Utomo (Journal of Politic and Government Studies, 2013)
ABSTRACTThis research was conducted to explain the evaluation result of theexistence of Pasar Ikan Higienis (PIH) Mina Rejomulyo. The potency ofprospective fisheries industry which is developing nowadays, especially in centralof java, is not supported by a good management system that makes the potencycannot be organized optimally due to such as: the distribution of fisheriesproducts, the hygiene process and storing, the lack of maximum distribution. Tomake the distribution of fishery industry which is able to give standard qualityand maximum hygiene in controll, it is important to build PIH that reflected as acentral process of modern trading by giving services and information optimally toall consumers completed with high quality and good hygiene products and also toimprove regional revenue sharing and social empowerment.In conducting this research, the writer used a qualitative reserarchmethod descriptive analysis study in order to explain the evaluation ofmanagement and developing policy of PIH Mina Rejomulyo and its feedback tothe people and local government. The subject of this research is department offishery as the local government of Semarang, specifically UPTD PIH MinaRejomulyo, Semarang local representative and its people. In conducting thisresearch, some methods are used in order to collect the data such as interview,observation, and document research.The result in this research showed that, for about six years until today(2012), the function of PIH Mina Rejomulyo and its financial contribution to thePAD is not optimally reached yet. The policy of PIH management depends on themoney supported by our local government and still cannot run individually.Besides, there are many problems found in managing PIH Rejomulyo related tothe lack of publicity or promotion that brings PIH close to the people.